Composite material, heat sink, and semiconductor package

By arranging the openings in the second layer of the composite material in a houndstooth grid and controlling the width and spacing of the openings, the problems of insufficient thermal conductivity of the existing composite materials and easy breakage of the molybdenum plate are solved, and lower linear expansion coefficient anisotropy and higher thermal conductivity are achieved.

CN119547205APending Publication Date: 2025-02-28SUMITOMO ELECTRIC INDUSTRIES LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380054049.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-04
Filing Date
2023-07-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

There is room for improvement in the thickness direction of the conventional composite materials, and when the opening diameter of the opening part is expanded to improve the thermal conductivity, the molybdenum plate is prone to breakage, resulting in an increase in the anisotropy of the linear expansion coefficient.

Method used

By placing the openings arranged in a houndstooth grid in the second layer of the composite material, and controlling the width and spacing of the openings, the continuity and thermal conductivity of the molybdenum plate are ensured.

Benefits of technology

The anisotropy of the linear expansion coefficient of the composite material is effectively reduced, and the thermal conductivity in the thickness direction is improved, while avoiding damage to the molybdenum plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547205A_ABST
    Figure CN119547205A_ABST
Patent Text Reader

Abstract

The composite material of the present invention is plate-shaped and has a first surface and a second surface which is an opposite surface to the first surface. The composite material has a plurality of first layers, and at least one second layer. The first surface and the second surface form end faces in the thickness direction of the composite material. The first layer and the second layer are alternately laminated in the thickness direction such that the first layer is located on the first surface and the second surface. The first layer is a layer of a metal material having copper as a main component. The second layer has a molybdenum plate and a copper filler. A plurality of openings penetrating the molybdenum plate in the thickness direction are formed in the molybdenum plate. The copper filler is disposed inside the opening. In a cross-sectional view orthogonal to the thickness direction, the openings are arranged so as to form a lattice arrangement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite material, a heat sink and a semiconductor package. The present invention claims priority based on Japanese patent application No. 2022-124936 filed on August 4, 2022. All the contents described in the Japanese patent application are incorporated herein by reference. Background Art

[0002] For example, International Publication No. 2022 / 030197 (Patent Document 1) describes a plate-shaped composite material. The composite material described in Patent Document 1 has a first surface and a second surface that is opposite to the first surface. The first surface and the second surface form end faces in the thickness direction (hereinafter referred to as the "thickness direction") of the composite material described in Patent Document 1.

[0003] The composite material described in Patent Document 1 has a plurality of first layers and a plurality of second layers. The first layer and the second layer are alternately stacked in the thickness direction in a manner that the first layer is located on the first surface and the second surface. The first layer is a layer of a metal material with copper as the main component. The second layer has a molybdenum plate and a copper filler. A plurality of openings are formed in the molybdenum plate. The openings penetrate the molybdenum plate in the thickness direction. The openings are circular when viewed from above and are arranged in a square lattice when viewed from above. The copper filler is arranged inside the opening.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: International Publication No. 2022 / 030197. Summary of the invention

[0007] The composite material of the present invention is in the form of a plate, having a first surface and a second surface as an opposite surface of the first surface. The composite material has a plurality of first layers and at least one second layer. The first surface and the second surface form end faces in the thickness direction of the composite material. The first layer and the second layer are alternately stacked in the thickness direction in such a manner that the first layer is located on the first surface and the second surface. The first layer is a layer of a metal material with copper as the main component. The second layer has a molybdenum plate and a copper filler. A plurality of openings penetrating the molybdenum plate in the thickness direction are formed in the molybdenum plate. The copper filler is arranged inside the opening. When observed in a cross-section perpendicular to the thickness direction, the openings are arranged in a manner forming a lattice arrangement. When observed in a cross-section perpendicular to the thickness direction, the openings have a first width in the row direction of the lattice arrangement, and have a second width in the column direction of the lattice arrangement perpendicular to the row direction. The first width is greater than 350 μm. The value obtained by dividing the second width by the first width is greater than 1 and less than 2. When observed in a cross-section perpendicular to the thickness direction, the molybdenum plate has a portion that is continuous along the first direction without interfering with the opening, and a portion that is continuous along the second direction different from the first direction without interfering with the opening. The angle formed by the first direction and the second direction is greater than or equal to 47° and less than or equal to 90°. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 is a perspective view of the composite material 10 .

[0009] Figure 2 yes Figure 1 Cross-sectional view at II-II.

[0010] Figure 3 yes Figure 2 Cross-sectional view at III-III in the figure.

[0011] Figure 4A This is a first explanatory diagram of a procedure for preparing a measurement sample of the thermal conductivity in the thickness direction of the composite material 10 .

[0012] Figure 4B This is a second explanatory diagram of the procedure for preparing a measurement sample of the thermal conductivity in the thickness direction of the composite material 10 .

[0013] Figure 4C This is a third explanatory diagram of the procedure for preparing a measurement sample of the thermal conductivity in the thickness direction of the composite material 10 .

[0014] Figure 5 It is a manufacturing process diagram of the composite material 10.

[0015] Figure 6 is an exploded perspective view of the semiconductor package 100 . DETAILED DESCRIPTION

[0016] [Problems to be Solved by the Invention]

[0017] In the composite material described in Patent Document 1, since the opening diameter of the opening is small, the thermal conductivity of the second layer in the thickness direction has room for improvement. If the opening diameter of the opening is enlarged in order to improve the thermal conductivity of the second layer in the thickness direction of the composite material described in Patent Document 1, the distance between two adjacent openings becomes smaller, and the molybdenum plate sometimes breaks between two adjacent openings. In order to avoid such breakage, it is considered to configure the openings in, for example, a houndstooth pattern. However, if the openings are configured in a houndstooth pattern, the anisotropy of the linear expansion coefficient in a plane orthogonal to the thickness direction sometimes becomes larger.

[0018] The present invention has been made in view of the above-mentioned problems of the prior art. More specifically, the present invention provides a composite material capable of reducing the anisotropy of the linear expansion coefficient in a plane perpendicular to the thickness direction.

[0019] [Effects of the Invention]

[0020] According to the composite material of the present invention, the anisotropy of the linear expansion coefficient in a plane perpendicular to the thickness direction can be reduced.

[0021] [Description of Embodiments of the Invention]

[0022] First, embodiments of the present invention will be listed and described.

[0023] (1) The composite material involved in the embodiment is in the form of a plate, having a first surface and a second surface which is the opposite surface of the first surface. The composite material has a plurality of first layers and at least one second layer. The first surface and the second surface form end faces of the composite material in the thickness direction. The first layer and the second layer are alternately stacked in the thickness direction in such a manner that the first layer is located on the first surface and the second surface. The first layer is a layer of a metal material having copper as a main component. The second layer has a molybdenum plate and a copper filler. A plurality of openings penetrating the molybdenum plate in the thickness direction are formed in the molybdenum plate. The copper filler is arranged inside the opening. When observed in a cross-section perpendicular to the thickness direction, the openings are arranged in a manner forming a lattice arrangement. When observed in a cross-section perpendicular to the thickness direction, the openings have a first width in the row direction of the lattice arrangement and a second width in the column direction of the lattice arrangement perpendicular to the row direction. The first width is greater than 350 μm. The value obtained by dividing the second width by the first width is greater than 1 and less than 2. When viewed in cross section perpendicular to the thickness direction, the molybdenum plate has a portion that is continuous in a first direction without interfering with the opening, and a portion that is continuous in a second direction different from the first direction without interfering with the opening. The angle between the first direction and the second direction is greater than 47° and less than 90°.

[0024] According to the composite material of (1) above, the anisotropy of the linear expansion coefficient in a plane perpendicular to the thickness direction can be reduced.

[0025] (2) In the composite material of (1) above, an angle formed by the first direction and the second direction is smaller than 90°.

[0026] (3) In the composite material of (1) or (2) above, when observed in a cross-section perpendicular to the thickness direction, every 1 mm 2 The number of openings may be less than three.

[0027] (4) In the composite material of (1) or (2) above, when observed in a cross-section perpendicular to the thickness direction, the thickness of the composite material is 2 The number of openings may be less than 2.

[0028] (5) In the composite materials of (1) to (4) above, the opening ratio of the molybdenum plate when observed in a cross section perpendicular to the thickness direction may be 20% or more.

[0029] (6) In the composite materials of (1) to (5) above, the volume ratio of molybdenum in the composite material may be 25% or less.

[0030] (7) In the composite materials of (1) to (5) above, the volume ratio of molybdenum in the composite material may be 15% or more. The composite material of (7) above can reduce the linear expansion coefficient.

[0031] (8) In the composite materials of (1) to (5) above, the volume ratio of molybdenum in the composite material may be less than 15%. The composite material of (8) above can increase thermal conductivity.

[0032] (9) In the composite materials of (1) to (8) above, the sum of the number of the first layers and the number of the second layers may be 5. The thickness of the composite material may be 1.5 mm or less. The thickness of the second layer may be 0.3 mm or less.

[0033] (10) In the composite materials of (1) to (9) above, the value obtained by dividing the linear expansion coefficient in the row direction when the temperature changes from room temperature to 800°C by the linear expansion coefficient in the column direction when the temperature changes from room temperature to 800°C can be 1.5 or less.

[0034] (11) In the composite materials of (1) to (10) above, a pitch between openings adjacent to each other in a column direction may be larger than a pitch between openings adjacent to each other in a row direction.

[0035] (12) A heat sink according to an embodiment includes the composite material of any one of (1) to (11). The first surface serves as a contact surface with a heat source.

[0036] (13) A semiconductor package according to an embodiment includes the composite material of any one of (1) to (11) above and a semiconductor element. The semiconductor element is disposed on the first surface.

[0037] (14) The semiconductor package of (13) above may further include a case member made of a ceramic material. The case member may be arranged on the first surface so as to surround the semiconductor element.

[0038] [Specific embodiments of the present invention]

[0039] Next, embodiments of the present invention will be described in detail with reference to the accompanying drawings. In the following drawings, the same reference numerals are used for the same or corresponding parts, and repeated descriptions are omitted. The composite material involved in the embodiment is referred to as composite material 10. The semiconductor package involved in the embodiment is referred to as semiconductor package 100.

[0040] (Structure of composite material 10)

[0041] Next, the structure of the composite material 10 will be described.

[0042] Figure 1 is a three-dimensional diagram of the composite material 10. Figure 1 As shown, the composite material 10 is in a plate shape. The thickness direction of the composite material 10 is referred to as the "thickness direction". The composite material 10 has a first surface 10a and a second surface 10b. The first surface 10a and the second surface 10b form end surfaces of the composite material 10 in the thickness direction. The second surface 10b is the opposite surface of the first surface 10a.

[0043] Figure 2 yes Figure 1 The cross-sectional view at II-II in FIG. Figure 2 As shown, the composite material 10 has a plurality of first layers 11 and at least one second layer 12. The first layer 11 and the second layer 12 are stacked in the thickness direction in such a manner that the first layer 11 is located on the first surface 10a and the second surface 10b. The thickness of the composite material 10 is set to thickness T1, and the thickness of the second layer 12 is set to T2. The thickness T1 is preferably less than 1.5 mm. The thickness T2 is preferably less than 0.3 mm, and more preferably less than 0.15 mm. The sum of the number of the first layers 11 and the number of the second layers 12 is more than 3. The number of the first layers 11 and the number of the second layers 12 are preferably 5.

[0044] The first layer 11 is a layer of a metal material with copper as the main component. "Metal material with copper as the main component" means a metal material with a copper content of 50% by mass or more. The first layer 11 is preferably a layer of a metal material with a copper content of 70% by mass or more. The first layer 11 is, for example, a layer of pure copper. Pure copper is a metal material composed of copper and inevitable impurities constituting the remainder.

[0045] The second layer 12 has a molybdenum plate 13 and a copper filler 14. The molybdenum plate 13 is a plate of a metal material with molybdenum as the main component. "Metal material with molybdenum as the main component" means a metal material with a molybdenum content of 50% by mass or more. The molybdenum plate 13 is preferably a plate of a metal material with a molybdenum content of 70% by mass or more. The molybdenum plate 13 is, for example, a plate of pure molybdenum. Pure molybdenum is a metal material formed of molybdenum and inevitable impurities constituting the remainder. The copper filler 14 is formed of, for example, the same material as the first layer 11.

[0046] Figure 3 yes Figure 2 The cross-sectional view at III-III in FIG. Figure 2 and Figure 3 As shown, a plurality of openings 13a are formed in the molybdenum plate 13. The openings 13a penetrate the molybdenum plate 13 in the thickness direction. When observed in a cross-section perpendicular to the thickness direction, the openings 13a are arranged in a lattice arrangement. More specifically, when observed in a cross-section perpendicular to the thickness direction, the openings 13a are arranged in a houndstooth pattern. When observed in a cross-section perpendicular to the thickness direction, the openings 13a may also be arranged in a square lattice or a rectangular lattice.

[0047] The row direction and column direction of the lattice arrangement of the openings 13a are respectively referred to as "row direction" and "column direction". The column direction is, for example, along the extension direction of the composite material 10. The column direction is, for example, orthogonal to the row direction. The pitch between the adjacent openings 13a in the row direction is referred to as a first pitch. The pitch between the adjacent openings 13a in the column direction is referred to as a second pitch. The second pitch is preferably larger than the first pitch.

[0048] The first pitch and the second pitch are measured through a cross section perpendicular to the thickness direction passing through the center of the molybdenum plate 13. The cross section perpendicular to the thickness direction passing through the center of the molybdenum plate 13 is exposed by the following process.

[0049] In the first step, the distance between the first surface 10a and the center of the thickness direction of the molybdenum plate 13 is measured by observing the composite material from the side using a digital microscope. In the second step, the composite material 10 is ground from the first surface 10a side using a surface grinder or an automatic rotary grinder. The grinding amount at this time is set to be equal to the distance between the first surface 10a and the center of the thickness direction of the molybdenum plate 13 measured in the above manner. As a result, a cross section passing through the center of the thickness direction of the molybdenum plate 13 and orthogonal to the thickness direction is exposed.

[0050] For all the openings 13a, the distances between the centers of the openings 13a adjacent to each other in the row direction are measured, and the sum of the measured values ​​is divided by the number of the openings 13a, thereby obtaining a first pitch. Similarly, for all the openings 13a, the distances between the centers of the openings 13a adjacent to each other in the column direction are measured, and the sum of the measured values ​​is divided by the number of the openings 13a, thereby obtaining a second pitch. A digital microscope is used for measuring the first pitch and the second pitch.

[0051] When observed in a cross-section perpendicular to the thickness direction, the opening 13a has a first width W1 as a width in the row direction, and a second width W2 as a width in the column direction. The first width W1 and the second width W2 are measured in a cross-section passing through the center of the thickness direction of the molybdenum plate 13 and perpendicular to the thickness direction. The width in the row direction is measured for all openings 13a, and the sum of the measured values ​​is divided by the number of openings 13a, thereby obtaining the first width W1. Similarly, the width in the column direction is measured for all openings 13a, and the sum of the measured values ​​is divided by the number of openings 13a, thereby obtaining the second width W2. The first width W1 is greater than 350μm. The value obtained by dividing the second width W2 by the first width W1 is greater than 1 and less than 2. A digital microscope is used in the measurement of the first width W1 and the second width W2.

[0052] When the opening 13a is observed in a cross-section perpendicular to the thickness direction, for example, the opening 13a is an ellipse. When the opening 13a is observed in a cross-section perpendicular to the thickness direction, the major axis of the ellipse is, for example, along the row direction. When the opening 13a is observed in a cross-section perpendicular to the thickness direction, the opening 13a may also be a circle. However, the cross-sectional shape of the opening 13a is not limited to these.

[0053] Every 1mm 2 The number of openings 13a is, for example, less than 3. 2 The number of openings 13a is preferably less than 2. The number of openings 13a in a cross section passing through the center of the thickness direction of the molybdenum plate 13 and perpendicular to the thickness direction is divided by the area of ​​the cross section (unit: mm 2 ), thus obtaining every 1mm 2 The number of openings 13a is .

[0054] The opening ratio of the molybdenum plate 13 is, for example, greater than 20%. The opening ratio of the molybdenum plate 13 may also be greater than 30% or greater than 35%. The opening ratio of the molybdenum plate 13 is, for example, less than 70%. The opening ratio of the molybdenum plate 13 may also be less than 60%. The sum of the opening areas of the openings 13a is measured in a cross section passing through the center of the thickness direction of the molybdenum plate 13 and orthogonal to the thickness direction, and the sum of the measured values ​​is divided by the area of ​​the cross section, thereby obtaining the opening ratio of the molybdenum plate 13. The opening area of ​​the opening 13a in the cross section passing through the center of the thickness direction of the molybdenum plate 13 and orthogonal to the thickness direction is measured using a digital microscope.

[0055] When viewed in a cross-section perpendicular to the thickness direction, the molybdenum plate 13 has a portion that is continuous along the first direction without interfering with the opening 13a, and a portion that is continuous along the second direction without interfering with the opening 13a. Figure 3 The direction of the straight line L1 in the second direction is Figure 3 The first direction and the second direction may be directions different from the column direction and the row direction. The angle between the first direction and the second direction is set to angle θ. Angle θ is an angle of 90° or less among the intersection angles of straight line L1 and straight line L2. Angle θ is greater than or equal to 47° and less than or equal to 90°. Angle θ is preferably greater than or equal to 47° and less than 90°. Angle θ is measured in a cross section passing through the center of the thickness direction of the molybdenum plate 13 and orthogonal to the thickness direction.

[0056] When there are three or more directions of the portion of the molybdenum plate 13 that is continuous without interfering with the opening 13 a , the direction in which the angle θ is smallest is selected from among the three or more directions.

[0057] The thermal conductivity in the thickness direction of the composite material 10 is preferably 270 W / m·K or more at room temperature. The thermal conductivity in the thickness direction of the composite material 10 is preferably 300 W / m·K or more at room temperature. "Room temperature" means 27°C.

[0058] The thermal conductivity in the thickness direction of the composite material 10 was measured using a laser flash method. In the laser flash method, the thermal diffusion coefficient of the composite material 10 was measured using LFA447 MicroFlash (manufactured by NETZSCH), and the thermal conductivity in the thickness direction of the composite material 10 was calculated based on the thermal diffusion coefficient and the volume ratio and specific heat of each constituent material of the composite material 10. When calculating the above thermal conductivity, the specific heat of each constituent material was determined according to the Metal Data Handbook 4th Edition (2004, Maruzen Publishing) compiled by the Japan Institute of Metals. In addition, before measuring the thermal conductivity of the composite material 10, the thermal conductivity of a pure copper sample of the same shape was measured under the same conditions, and the result was used as a reference to correct the measurement result.

[0059] Figure 4A1 is a first explanatory diagram of the procedure for preparing a measurement sample of the thermal conductivity in the thickness direction of the composite material 10. Figure 4A As shown, a thin piece 15 is cut out from the composite material 10 to be measured. The thickness, length, and width of the thin piece 15 are t (mm), B (mm), and C (mm), respectively.

[0060] The number obtained by rounding up the decimal part of the value obtained by dividing 2 by t is X. The number obtained by rounding up the decimal part of the value obtained by dividing 10 by B is Y1. The number obtained by rounding up the decimal part of the value obtained by dividing 10 by C is Y2. The number of sheets 15 equal to the product of X, Y1 and Y2 is cut out from the composite material 10 to be measured.

[0061] Figure 4B 2 is a second explanatory diagram of the procedure for preparing a measurement sample of the thermal conductivity in the thickness direction of the composite material 10. Figure 4B As shown, block 16 is made using X-sheet sheets 15. The thickness, length, and width of block 16 are approximately 2 (mm), B (mm), and C (mm), respectively. In the production of block 16, the first step is to stack X-sheet sheets 15. At this time, amorphous powder formed of pure silver with an average particle size of 4 μm is arranged between adjacent sheets 15. The amount of amorphous powder arranged between adjacent sheets 15 is 100 mm 2 0.2g±30%.

[0062] In the production of block 16, in the second step, a rectangular mold (not shown) with an opening having inner dimensions of B (mm) × C (mm) is prepared, and the stacked thin sheets are arranged in the opening. The above-mentioned mold is made of graphite. In the production of block 16, in the third step, the stacked thin sheets 15 are heat treated under a load P. The load P is greater than 4.9N and less than 9.8N. The heat treatment is carried out in an inert gas environment. The heat treatment is carried out at a holding temperature of 900°C and a holding time of 10 minutes. Through the heat treatment, the amorphous powder softens and deforms to bond adjacent thin sheets 15, thereby producing block 16.

[0063] Figure 4C 3 is a third explanatory diagram of the procedure for preparing a measurement sample of the thermal conductivity in the thickness direction of the composite material 10. Figure 4CAs shown, by arranging Y1 blocks 16 in the longitudinal direction and Y2 blocks 16 in the transverse direction, a measurement sample 17 with a height of about 10 mm, a width of about 10 mm, and a thickness of about 2 mm is prepared. When Y1 blocks 16 are arranged in the longitudinal direction and Y2 blocks 16 are arranged in the transverse direction, the adjacent blocks 16 are bonded to each other using an adhesive member. As the adhesive member, a material that can withstand a temperature of about 800° C., such as silver brazing foil and ceramic adhesive, can be used. The blocks 16 arranged in the longitudinal direction and Y2 blocks arranged in the transverse direction can also be fixed by winding a stainless steel wire or the like around the periphery thereof.

[0064] The linear expansion coefficient of the composite material 10 in the row direction when the temperature changes from room temperature to 800° C. (first linear expansion coefficient) and the linear expansion coefficient of the composite material 10 in the column direction when the temperature changes from room temperature to 800° C. (second linear expansion coefficient) are preferably 14 ppm / K or less. The first linear expansion coefficient and the second linear expansion coefficient are more preferably 10 ppm / K or less. The value obtained by dividing the first linear expansion coefficient by the second linear expansion coefficient is preferably 1.5 or less.

[0065] The displacements in the row and column directions of the composite material 10 in the temperature range from room temperature to 800° C. were measured using TD5000SA (manufactured by Bruker AXS) to calculate the first linear expansion coefficient and the second linear expansion coefficient. When calculating the first linear expansion coefficient and the second linear expansion coefficient, the plane shape of the composite material 10 was a rectangular shape of 3 mm×15 mm. The measured value was the average value of three samples.

[0066] The volume ratio of molybdenum in the composite material 10 is, for example, 25% or less. From the viewpoint of improving the thermal conductivity in the thickness direction of the composite material 10, the volume ratio of molybdenum in the composite material 10 is preferably 15% or more. On the other hand, from the viewpoint of reducing the linear expansion coefficient of the composite material 10, the volume ratio of molybdenum in the composite material 10 is preferably less than 15%.

[0067] (Method for Manufacturing Composite Material 10)

[0068] Next, a method for producing the composite material 10 will be described.

[0069] Figure 5 1 is a manufacturing process diagram of the composite material 10. Figure 5 As shown, the manufacturing method of the composite material 10 includes a preparation step S1, a hole-making step S2, and a rolling step S3. In the preparation step S1, a first plate and a second plate are prepared. The first plate is a plate made of a metal material with copper as the main component. The second plate is a plate made of a metal material with molybdenum as the main component.

[0070] In the hole punching step S2, the second plate is punched. Through the hole punching, a plurality of openings penetrating the second plate in the thickness direction are formed in the second plate. As a result, the second plate becomes the molybdenum plate 13. For example, the second plate is punched by etching or laser irradiation.

[0071] In the rolling process S3, the first step is to prepare the stacked body 20. The stacked body 20 is prepared by alternately arranging the first plate and the molybdenum plate 13 in the thickness direction of the stacked body 20. In the rolling process S3, the second step is to heat treat the stacked body 20. In this heat treatment, the stacked body 20 is heated to a predetermined temperature in a hydrogen atmosphere. The predetermined temperature is set to a temperature that is lower than the melting point of the first plate and makes the first plate sufficiently softened. The predetermined temperature is, for example, 900°C.

[0072] In the rolling process S3, in the third step, the laminate 20 is passed through the rolling rollers. Thus, the first plate and the molybdenum plate 13 are joined to each other while being rolled. At this time, since the first plate flows, the first plate is filled in the opening 13a of the molybdenum plate 13 to form the copper filler 14. The remaining part of the first plate that is not filled in the opening 13a forms the first layer 11. Thus, a copper filler 14 is produced. Figure 2 Composite material 10 of the structure shown. From another point of view, in composite material 10, first layer 11 and second layer 12 are joined by hot rolling joining method.

[0073] In addition, the method for producing the composite material 10 may further include a rolling step S4. The rolling step S4 is performed after the heating step S3. In the rolling step S4, the composite material 10 is cold-rolled to adjust the thickness T1.

[0074] (Structure of Semiconductor Package 100)

[0075] Hereinafter, the structure of the semiconductor package 100 will be described.

[0076] Figure 6 FIG. 1 is an exploded perspective view of the semiconductor package 100. Figure 6 As shown, the semiconductor package 100 includes a composite material 10 , a semiconductor element 30 , a case member 40 , a cover 41 , a terminal 50 a , and a terminal 50 b .

[0077] The composite material 10 functions as a heat sink in the semiconductor package 100. The semiconductor element 30 is disposed on the first surface 10a. A heat conducting member may be interposed between the semiconductor element 30 and the first surface 10a. The semiconductor element 30 becomes a heat source when operating.

[0078] The shell member 40 is made of, for example, a ceramic material. The ceramic material is, for example, alumina (Al2O3). The shell member 40 is arranged on the first surface 10a so as to surround the semiconductor element 30. The lower end (the end on the first surface 10a side) of the shell member 40 is joined to the first surface 10a, for example, by brazing. The cover 41 is made of, for example, a ceramic material or a metal material. The cover 41 closes the upper end side of the shell member 40.

[0079] The terminal 50a and the terminal 50b are inserted into the housing member 40. As a result, one end of the terminal 50a and the terminal 50b is located in the space defined by the first surface 10a, the housing member 40 and the cover 41, and the other end of the terminal 50a and the terminal 50b is located outside the space. The terminal 50a and the terminal 50a are made of, for example, a metal material. The metal material is, for example, Kovar.

[0080] Although not shown, one end side of the terminal 50a and the terminal 50b is electrically connected to the semiconductor element 30. The semiconductor package 100 is electrically connected to another device or circuit different from the semiconductor package 100 at the other end side of the terminal 50a and the terminal 50b.

[0081] A heat dissipation member 60 is mounted on the second surface 10b. The heat dissipation member 60 is, for example, a metal plate having a flow path for a coolant flowing therein. However, the heat dissipation member 60 is not limited thereto. The heat dissipation member 60 may also be a cooling blade. A heat conduction member may also be sandwiched between the heat dissipation member 60 and the second surface 10b.

[0082] (Effects of the composite material 10)

[0083] Next, the effects of the composite material 10 will be described.

[0084] As described above, the shell member 40 is joined to the composite material 10 by brazing or the like. Therefore, in order to reduce the thermal stress caused by the difference between the linear expansion coefficients of the composite material 10 and the shell member 40, the linear expansion coefficients of the composite material 10 and the shell member 40 are preferably close to each other.

[0085] In addition, when the linear expansion coefficient of the composite material 10 is anisotropic, even if the linear expansion coefficient of the composite material 10 in a certain direction (for example, the column direction) is close to the linear expansion coefficient of the shell component 40, the difference between the linear expansion coefficient of the composite material 10 in other directions (for example, the row direction) and the linear expansion coefficient of the shell component 40 will also become larger.

[0086] Since the linear expansion coefficient of molybdenum is smaller than that of copper, the linear expansion coefficient of the composite material 10 tends to be smaller in the direction in which the portion of the molybdenum plate 13 that is continuous and does not interfere with the opening 13a extends. Therefore, the larger the angle θ, the smaller the anisotropy of the linear expansion coefficient of the composite material 10. On the other hand, the smaller the angle θ, the larger the distance between adjacent openings 13a, and the molybdenum plate 13 is likely to break between adjacent openings 13a during rolling.

[0087] In addition, when the first width W1 is set larger (specifically, greater than 350 μm) and the value obtained by dividing the second width W2 by the first width W1 is greater than or equal to 1 and less than or equal to 2, the heat generated by the semiconductor element 30 as a heat source passes through the second layer 12, and it becomes easy to pass through the copper filler 14, so the thermal resistance of the second layer 12 is reduced. However, in this case, since the distance between adjacent openings 13a becomes shorter, the molybdenum plate 13 is easily broken between adjacent openings 13a during rolling.

[0088] After in-depth research, the inventors of the present invention found that when the angle θ is greater than 47° and less than 90°, even if the first width W1 is greater than 350μm and the value obtained by dividing the second width W2 by the first width W1 is greater than 1 and less than 2, the breakage of the molybdenum plate 13 between adjacent openings 13a can be suppressed, and the anisotropy of the linear expansion coefficient of the composite material 10 can be reduced.

[0089] (Example)

[0090] Samples 1 to 7 were prepared as samples of the composite material. As shown in Table 1, in Samples 1 to 7, the angle θ, the first width W1, the second width W2, the first pitch, the second pitch, and the distance per 1 mm 2 The number of openings 13a and the opening ratio of the molybdenum plate 13 are changed. In samples 1 to 7, the first layer 11 is a pure copper layer, and the molybdenum plate 13 is a pure molybdenum plate. In samples 1 to 7, the number of the first layer 11 is 3, and the number of the second layer 12 is 2.

[0091] As shown in Table 2, in Samples 1 to 7, the thickness of the first plate material and the thickness of the molybdenum plate 13 before rolling are adjusted, and the reduction rate during rolling is adjusted to adjust the thickness T1 and the volume ratio of molybdenum. The reduction rate during rolling is appropriately adjusted in a manner that does not cause internal fracture of the material. In addition, the thickness of the first plate material shown in Table 2 is the thickness of the first plate material located on the outermost surface of the stacked body 20.

[0092] [Table 1]

[0093]

[0094] [Table 2]

[0095] Table 2

[0096]

[0097] The angle θ is 47° or more and 90° or less as condition A. The first width W1 is 350 μm or more as condition B. The value obtained by dividing the second width W2 by the first width W1 is 1 or more and 2 or less as condition C. In samples 1 to 4, conditions A to C are all satisfied. On the other hand, in samples 5 to 7, at least any one of conditions A to C is not satisfied.

[0098] The first linear expansion coefficient, the second linear expansion coefficient, and the thermal conductivity in the thickness direction were measured for Samples 1 to 7. As shown in Table 3, in Samples 1 to 4, the value obtained by dividing the first linear expansion coefficient by the second linear expansion coefficient was 1.5 or less. On the other hand, in Samples 5 to 7, the value obtained by dividing the first linear expansion coefficient by the second linear expansion coefficient was greater than 1.5.

[0099] [Table 3]

[0100] Table 3

[0101]

[0102] Through this comparison, the experiment shows that the anisotropy of the linear expansion coefficient of the composite material 10 can be reduced by satisfying conditions A to C. In addition, in samples 1 to 4, the first linear expansion coefficient and the second linear expansion coefficient are both 14 ppm or less, but in samples 5 to 7, the first linear expansion coefficient is greater than 14 ppm.

[0103] In Samples 1 and 2, the volume ratio of molybdenum is less than 15%, but in Samples 3 and 4, the volume ratio of molybdenum is 15% or more. In Samples 1 and 2, the first linear expansion coefficient and the second linear expansion coefficient are both less than 10 ppm. In Samples 3 to 4, the first linear expansion coefficient is greater than 10 ppm. In Samples 1 and 2, the thermal conductivity in the thickness direction is 270 W / m·K or more and less than 300 W / m·K. In Samples 3 and 4, the thermal conductivity in the thickness direction is 300 W / m·K or more.

[0104] This comparison experimentally shows that the linear expansion coefficient of the composite material 10 can be reduced by making the volume ratio of molybdenum less than 15%, and the thermal conductivity of the composite material 10 can be reduced by making the volume ratio of molybdenum greater than 15%.

[0105] The embodiments disclosed herein are illustrative in all respects and are not intended to be limiting. The scope of the present invention is not indicated by the above embodiments but by the scope of the claims, and is intended to include all modifications within the meaning and scope equivalent to the scope of the claims.

[0106] Description of Reference Numerals

[0107] 10a: first surface; 10b: second surface; 11: first layer; 12: second layer; 13: molybdenum plate; 13a: opening; 14: copper filler; 15: sheet; 16: block; 17: measurement sample; 20: laminate; 30: semiconductor element; 40: housing member; 41: cover; 50a, 50b: terminal; 60: heat dissipation member; 10: composite material; 100: semiconductor package; S1: preparation process; S2: hole opening process; S3, S4: rolling process; T1, T2: thickness; L1, L2: straight line; P: load; W1: first width; W2: second width.

Claims

1. A composite material in a plate shape having a first surface and a second surface opposite to the first surface, The composite material has a plurality of first layers and at least one second layer, The first surface and the second surface form end surfaces in the thickness direction of the composite material, The first layer and the second layer are alternately stacked along the thickness direction in a manner such that the first layer is located on the first surface and the second surface. The first layer is a layer of metal material with copper as the main component, The second layer has a molybdenum plate and a copper filler, The molybdenum plate is formed with a plurality of openings penetrating the molybdenum plate in the thickness direction. The copper filler is arranged inside the opening, When viewed in a cross-section perpendicular to the thickness direction, the openings are arranged in a lattice pattern. When viewed in a cross-section perpendicular to the thickness direction, the opening has a first width in a row direction of the lattice arrangement and a second width in a column direction of the lattice arrangement perpendicular to the row direction. The first width is greater than 350 μm, A value obtained by dividing the second width by the first width is greater than or equal to 1 and less than or equal to 2. When viewed in a cross-section perpendicular to the thickness direction, the molybdenum plate has a portion that is continuous along a first direction without interfering with the opening, and a portion that is continuous along a second direction different from the first direction without interfering with the opening. An angle formed by the first direction and the second direction is greater than or equal to 47° and less than or equal to 90°.

2. The composite material according to claim 1, wherein An angle formed by the first direction and the second direction is smaller than 90°.

3. The composite material according to claim 1 or 2, wherein When viewed in a cross-section perpendicular to the thickness direction, every 1 mm 2 The number of the openings is less than 3.

4. The composite material according to claim 1 or 2, wherein When viewed in a cross-section perpendicular to the thickness direction, every 1 mm 2 The number of the openings is less than 2.

5. The composite material according to any one of claims 1 to 4, wherein The molybdenum plate has an opening ratio of 20% or more when viewed in a cross section perpendicular to the thickness direction.

6. The composite material according to any one of claims 1 to 5, wherein The volume ratio of molybdenum in the composite material is 25% or less.

7. The composite material according to any one of claims 1 to 5, wherein The volume ratio of molybdenum in the composite material is greater than 15%.

8. The composite material according to any one of claims 1 to 5, wherein The volume ratio of molybdenum in the composite material is less than 15%.

9. The composite material according to any one of claims 1 to 8, wherein The sum of the number of the first layer and the number of the second layer is 5, The thickness of the composite material is less than 1.5 mm, The thickness of the second layer is less than 0.3 mm.

10. The composite material according to any one of claims 1 to 9, wherein A value obtained by dividing the linear expansion coefficient in the row direction when the temperature changes from room temperature to 800° C. by the linear expansion coefficient in the column direction when the temperature changes from room temperature to 800° C. is 1.5 or less.

11. The composite material according to any one of claims 1 to 10, wherein A pitch between the adjacent openings in the column direction is larger than a pitch between the adjacent openings in the row direction. 12 . A heat sink comprising the composite material according to claim 1 , wherein the first surface serves as a contact surface with a heat source.

13. A semiconductor package comprising: The composite material according to any one of claims 1 to 11; and semiconductor components, The semiconductor element is disposed on the first surface.

14. The semiconductor package according to claim 13, wherein It also has: a shell component made of ceramic material, The housing member is arranged on the first surface so as to surround the semiconductor element.

Citation Information

Patent Citations

  • Batter flour set for deep-fried chicken

    JP2022124936A

  • Compoiste material, heat spreader and semiconductor package

    WO2022030197A1